2020
DOI: 10.1590/0102-311x00129620
|View full text |Cite
|
Sign up to set email alerts
|

Multimorbidade e população em risco para COVID-19 grave no Estudo Longitudinal da Saúde dos Idosos Brasileiros

Abstract: O objetivo deste trabalho foi medir a ocorrência de multimorbidade e estimar o número de indivíduos na população brasileira com 50 anos ou mais em risco para COVID-19 grave. Estudo transversal de base nacional com dados do Estudo Longitudinal da Saúde dos Idosos Brasileiros (ELSI-Brasil), conduzido em 2015-2016, com 9.412 indivíduos com 50 anos ou mais. A multimorbidade foi caracterizada como ≥ 2 condições crônicas com base em uma lista de 15 morbidades consideradas de risco para COVID-19 grave. As análises in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
32

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 30 publications
1
13
0
32
Order By: Relevance
“…Also, they showed a significant hazard ratio for BMI 40 kg/m 2 associated with higher mortality risk [8]. Nunes et al, 2020 measure the occurrence of multimorbidity to estimate the number of individuals in the Brazilian population 50 years or older at risk for severe COVID-19 [4]. They observed that among a list of 15 diseases considered risk conditions for severe COVID-19, cardiovascular diseases and obesity were the most frequent chronic conditions [4].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, they showed a significant hazard ratio for BMI 40 kg/m 2 associated with higher mortality risk [8]. Nunes et al, 2020 measure the occurrence of multimorbidity to estimate the number of individuals in the Brazilian population 50 years or older at risk for severe COVID-19 [4]. They observed that among a list of 15 diseases considered risk conditions for severe COVID-19, cardiovascular diseases and obesity were the most frequent chronic conditions [4].…”
Section: Resultsmentioning
confidence: 99%
“…Nunes et al, 2020 measure the occurrence of multimorbidity to estimate the number of individuals in the Brazilian population 50 years or older at risk for severe COVID-19 [4]. They observed that among a list of 15 diseases considered risk conditions for severe COVID-19, cardiovascular diseases and obesity were the most frequent chronic conditions [4]. Carneiro et al, 2021 observed a positive correlation between the prevalence of overweight/obesity and the overall mortality due to COVID-19 in 26 state capitals and the Federal District of Brazil [9].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…No Brasil, uma análise recente do estudo Longitudinal de Saúde do Idoso (ELSI-Brasil) mostrou que cerca de 34 milhões de pessoas com mais de 50 anos de idade têm ≥1 morbidade de risco para COVID-19 grave, com distribuição similar entre as regiões. As morbidades, relacionadas à COVID-19 grave, mais prevalentes nesse grupo foram: as doenças cardiovasculares (56%), obesidade (39%), artrite (21%) e depressão (18,5%) (6) .…”
Section: Resultsunclassified
“…Especificamente, entre os idosos, a alocação de recursos durante a pandemia pode ser um desafio ainda maior, pois trata-se do grupo com maior risco de desenvolver complicações graves da doença (6) , demandando recursos de diversas complexidades e níveis de atenção. Em todos os ambientes de cuidado, para idosos com limitações, haverá maior demanda de tempo de cuidados profissionais, especialmente da equipe de enfermagem (7) .…”
Section: Introductionunclassified